Niveles de contaminacion fungica en materias primas y piensos usados en la avicultura - Masdeu, F.V.=700 1 Garcia, C.M.; Miranda, L.Y.; Derivet, H.T.; Hernat, L.R.; Argote, R.C.
(Es, En)
Ilus., 12 ref.
Keywords: AVES DE CORRAL; PIENSOS; ZEA MAY; GLYCINE MAX; CONTAMINACION BIOLOGICA; HONGOS; CUBA